PENGARUH KEBIJAKAN, PERATURAN, LOCUS OF CONTROL DAN SIFAT MACHIEVELLIAN TERHADAP PERENCANAAN PAJAK ORANG PRIBADI - Yudi, Antony; handoko, jesica (Jurnal Akuntansi Kontemporer, 2018)
Tax planning is an attempt to minimize taxpayer tax due legally by using taxation legislation. With self assessment system, taxpayer can do tax planning. Literature shows that there are external factors like taxation legislation. Other side there are internal factors from someone like Machievellian and Locus of Control which motivates taxpayer to tax planning. Taxpayer sometimes will obey to pay taxes, if they argue that tax system is not fair. So that, one of way to avoid taxes is tax planning. Taxpayer who can do tax planning is professional freelance. The research proved that the tax policy, tax laws have significant impact on tax planning individual taxpayer. Otherside, Machievellian, Locus of Control have not significant impact on tax planning individual taxpayer.